Aperture effects on the oxygen abundance determinations from Califa data - Iglesias Páramo, J. (2016)
This paper aims to provide aperture corrections for emission lines in a sample of spiral galaxies from the Calar Alto Legacy Integral Field Area Survey (CALIFA) database. In particular, we explore the behavior of the log([O iii] λ5007/Hβ)/([N ii] λ6583/Hα) (O3N2) and log[N ii] λ6583/Hα (N2) flux ratios since they are closely connected to different empirical calibrations of the oxygen abundances in star-forming galaxies. We compute the median growth curves of Hα, Hα/Hβ, O3N2, and N2 up to 2.5R 50 and 1.5 disk . These distances cover most of the optical spatial extent of the CALIFA galaxies. The growth curves simulate the effect of observing galaxies through apertures of varying radii. We split these growth curves by morphological types and stellar masses to check if there is any dependence on these properties. The median growth curve of the Hα flux shows a monotonous increase with radius with no strong dependence on galaxy inclination, morphological type, and stellar mass. The median growth curve of the Hα/Hβ ratio monotonically decreases from the center toward larger radii, showing for small apertures a maximum value of ≈10% larger than the integrated one. It does not show any dependence on inclination, morphological type, and stellar mass. The median growth curve of N2 shows a similar behavior, decreasing from the center toward larger radii. No strong dependence is seen on the inclination, morphological type, and stellar mass. Finally, the median growth curve of O3N2 increases monotonically with radius, and it does not show dependence on the inclination. However, at small radii it shows systematically higher values for galaxies of earlier morphological types and for high stellar mass galaxies. Applying our aperture corrections to a sample of galaxies from the SDSS survey at 0.02 ≤ z ≤ 0.3 shows that the average difference between fiber-based and aperture-corrected oxygen abundances, for different galaxy stellar mass and redshift ranges, reaches typically to ≈11%, depending on the abundance calibration used. This average difference is found to be systematically biased, though still within the typical uncertainties of oxygen abundances derived from empirical calibrations. Caution must be exercised when using observations of galaxies for small radii (e.g., below 0.5 ) given the high dispersion shown around the median growth curves. Thus, the application of these median aperture corrections to derive abundances for individual galaxies is not recommended when their fluxes come from radii much smaller than either R 50 or Reff.